Urban Transportation in Chinese Cities: An Efficiency Assessment - Wei, J.; Xia, W.; Guo, Xiumei; Marinova, Dora (Pergamon, 2013)
We use 2008 data for 34 Chinese cities to compare urban transportation systems. The results show stronger eastern and central cities focusing more on high capacity and less on sustainable modes of transportation, while western cities do the opposite. Chinese cities with more sustainable transportation are also more likely to have lower gross domestic product per capita, be smaller, are less urbanized and have higher bus usage. This model needs to change to align with China’s new policy priorities.